Spiritual Meaning-Making and Cultural Encounter in Arabic Language Learning: An Interpretive Study of Indonesia’s Love-Based Curriculum in the Era of Educational Media and Technology - Muhammad Ainul Yaqin (Learning, Media and Technology in Arabic Education, 2025)
Background: Arabic language learning in Indonesia has traditionally emphasized grammar and structural mastery, often separating linguistic instruction from learners’ spiritual motivation and cultural experience. In response, the Love-Based Curriculum seeks to reposition Arabic learning as a meaningful, value-oriented, and contextually grounded process. Despite its growing adoption, the conceptual foundations of this curriculum and its relevance within contemporary learning environments, including media- and technology-supported contexts, remain underexplored. Aims: This study aims to interpret how the Love-Based Curriculum integrates spiritual meaning-making and socio-cultural engagement into Arabic language learning and to examine how these dimensions may be supported within contemporary educational media and technology contexts to enhance learner motivation, character development, and communicative engagement. Methods: The study employs an interpretive, literature-based qualitative approach. Academic publications, curriculum policy documents, and theoretical works on holistic pedagogy, applied linguistics, cultural literacy, spirituality in education, and technology-mediated learning were analyzed using thematic content analysis to construct a coherent conceptual framework. Results: The analysis suggests that spiritual reflection fosters a deeper sense of purpose in learning Arabic, while cultural encounter strengthens learners’ confidence and communicative participation. Together, these elements form an integrated pedagogical orientation that moves beyond mechanical instruction. Educational media and digital technologies are conceptually positioned as mediating tools that can extend reflective practice, cultural interaction, and value-based learning when aligned with the curriculum’s spiritual and ethical orientation. Conclusion: The Love-Based Curriculum offers a theoretically grounded framework for Arabic language education by integrating spiritual depth, cultural awareness, and the potential of media- and technology-supported learning. Its conceptual contributions enrich discussions on holistic and value-based pedagogy in Arabic education, while future empirical research is recommended to examine classroom enactment and technology integration.